The Socio – Economic Development Of India With Respect To Benefits From Commercial Exploitation Of Traditional Medicines And Its Protection - S. USHA,; C. ANNADURAI, (International Journal of Pharma and Bio Sciences, 2012)
This paper discusses the origin of various knowledge sources, the traditional knowledge (TK) in general and the same with respect to medicines, its product value across the globe and the percentage of complementary and alternative medicines (CAM) users in developed countries, where India stands in terms of usage as well as production to foreign markets. Importantly, it examines the socio – economic benefits arising out of the same, India’s place in the market at a global level in spite of it being the richest with natural resources as well as vast knowledge assets. The knowledge here is intellectual property. This paper proposes some of the remedies in the protection and rights of the knowledge and the communities which have become of prime importance. Hence there is a need to give priority in controlling this problem of erroneous exploitation of TK in India to the maximum extent possible with various legal and marketing strategies.